(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Efficient coordination of bus intervals is crucial for enhancing public transportation systems. This study explores methodologies for optimizing bus schedules to minimize waiting times, ensure timely arrivals, and improve overall passenger satisfaction. By employing mathematical modeling, simulation techniques, and real-time data analytics, we aim to develop a robust framework for synchronizing bus intervals in urban areas